Evaluation of the Open ERP Implementation for MSME (Case Study: Palembang City) - Mirza, Ahmad Haidar; Halim, R.M. Nasrul; Yeni, Yeni (Journal of Information System and Informatics, 2024)
The emergence of Enterprise Resource Planning (ERP) systems has transformed the way businesses operate, particularly for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. Serves as a relevant area of study to understand the impact, challenges, and benefits of using Open ERP. ERP is a method used by industries to enhance business process efficiency. This is done by sharing information both within and between business processes. This study aims to evaluate the implementation of Open ERP in the MSME ecosystem using the HOT-Fit method, which measures the fit between Human, Organization, and Technology components in the use of the Odoo application for MSMEs. Odoo is a open-source ERP software that is suitable for small and medium businesses. Based on the analysis results, it can be concluded that the implementation of OpenERP using the Odoo application only affects the human component. Simultaneous testing indicates that these three variables collectively influence net benefits.